2018
DOI: 10.1080/00405000.2018.1492339
|View full text |Cite
|
Sign up to set email alerts
|

Air permeability and bursting strength of weft-knitted fabrics from glass yarn. Part I: cam setting and number of yarn ply effect

Abstract: This study revealed the effect of cam setting and number of yarn ply on air permeability and bursting strength of weft-knitted fabrics from glass yarn. Change in cam setting from loose to tight level increased fiber content, and stitch-density; while it decreased loop length. Fabrics with 3-ply yarn exhibited higher fiber content; lower stitch-density; and longer loop length than fabrics with 2-ply yarn. Cam setting showed more pronounced effect on physical properties of fabric than number of yarn ply. Fabrics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…Furthermore, the effect of the number of yarn ply on thickness and areal density of the fabrics was also influential. This was described in our previous study, published online on JOTI (Ince & Yildirim, 2018). Similarly, knit patterns, except for those with tuck stitches, exhibited negative correlation in pairs of 'loop length-thickness' and 'loop length-areal density'.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…Furthermore, the effect of the number of yarn ply on thickness and areal density of the fabrics was also influential. This was described in our previous study, published online on JOTI (Ince & Yildirim, 2018). Similarly, knit patterns, except for those with tuck stitches, exhibited negative correlation in pairs of 'loop length-thickness' and 'loop length-areal density'.…”
Section: Resultssupporting
confidence: 78%
“…The knit patterns of weft-inlay, single jersey and skip stiches displayed a negative moderately strong relationship between loop length and thickness, while structures with tuck stitches displayed a positive strong relationship ( Figure 9 left, Table 7 first row block). Our previous study, published online in the JOTI (Ince & Yildirim, 2018), indicated that loose fabric cam setting (#8), and 3-ply yarn, increased loop length, as compared with tight fabric cam setting (#3) and 2-ply yarn ( Figure 10). Following examination of the relationships between 'loop lengththickness' and 'loop length -areal density', it was seen that the number of yarn ply was dominant over cam setting for structures with tuck stitches.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…It is known that the knitting structures are consist of loops of stitch yarns whose main function is to bind the insertion yarns together. The types of knitting structure 6,7 and the kinds of stitch yarn determine the properties of composites. The interlaminar properties of aramid binding and polyester binding multilayered biaxial weft knitted (MBWK) fabric reinforced epoxy composites were experimentally investigated by Qi et al 8 They found that the higher tensile strength of stitch yarn, the higher bending and interlaminar shear properties of the MBWK fabric reinforced composites.…”
Section: Introductionmentioning
confidence: 99%